IDENTIFIKASI PERMASALAHAN DALAM PENGELOLAAN WILAYAH SUNGAI DI JAWA TIMUR - Apriliani, Adini; Murti, Restu Hikmah Ayu; Irawanto, Rony (Envirous, 2025)
River basins are the most fundamental thing in managing natural water resources in Indonesia. Based on the Regulation of the Minister of Public Works and Public Housing No. 4/PRT/M/2015 concerning standards and ratification of river basins, Indonesia is divided into 128 river basins. The division of East Java is divided into 5 River Basins, namely the Madura Islands WS, Welang - Rejoso WS, Bondoyudo - Bedadung WS, Pekalen-Sampean WS, and Baru - Bajulmati WS. The condition of the river basin is increasingly causing various problems. The methods applied include a qualitative approach. The quantitative approach is carried out through the use of questionnaires filled out by participants followed by conducting a literature review. The results obtained from 48 respondents that the problems in the East Java river basin occurred due to flooding with a percentage of 66.67%, garbage 14.58%, waste 16.67%, and erosion 2.08%. From these problems there are solutions using biotechnology, river ecosystem restoration, wastewater management, dam construction with good infrastructure, the need for river basin monitoring sensors. Other essential factors in the socialization of education and community involvement are NGOs and government regulations.